Cellular and molecular mechanisms in fibrosis. Issue 1 (9th October 2020) - Dees, Clara; Chakraborty, Debomita; Distler, Jörg H. W.
Abstract: The activation of fibroblasts is required for physiological tissue remodelling such as wound healing. However, when the regulatory mechanisms are disrupted and fibroblasts remain persistently activated, the progressive deposition of extracellular matrix proteins leads to tissue fibrosis, which results in dysfunction or even loss of function of the affected organ. Although fibrosis has been recognized as a major cause of morbidity and mortality in modern societies, there are only few treatment options available that directly disrupt the release of extracellular matrix from fibroblasts. Intensive research in recent years, however, identified several pathways as core fibrotic mechanisms that are shared across different fibrotic diseases and organs. We discuss herein selection of those core pathways, especially downstream of the profibrotic TGF‐β pathway, which are druggable and which may be transferable from bench to bedside.